(untitled) (Revista Argentina de Cirugía, 2022)
Background: There exist clinical-pathological discrepancies at the staging after neoadyuvant therapy of rectal cancer, and there are currently no additional useful methods to distinguish the presence or absence of viable tumor. Objective: To determine the value of magnetic resonance diffusion imaging technique in the identification of the pathological complete response after the neoadyuvant therapy and to determine its relationship with the degree of clinical response. Setting: Private Community Hospital. Design: Retrospective Population: 24 patients (10 women), median age: 61, operated on for rectal cancer from June 2009 to January 2011. Outcome measures: According to the clinical response, patients grouped in responders and non-responders. All apparent diffusion coefficient value greater than 1.2 ´ 10-3 mm2/seg was regarded as pathological response. Results: Median of apparent diffusion coefficient was 1.1 (0.7 and 2 range).